Validity and Advantages of Three-Dimensional High-Frequency Ultrasound in Dermatological Evaluation - Misaki Kinoshita-Ise; Taiichiro Ida; Tatsuro Iwasaki; Hideaki Iwazaki; Kazuyuki Yokota; Hoshito Taguchi; Manabu Ohyama (Diagnostics)
Background/Objectives: High-frequency ultrasound (HFUS) has been reported to be useful for the diagnosis of cutaneous diseases; however, its two-dimensional nature limits the value both in quantitative and qualitative evaluation. Three-dimensional (3D) visualization might help overcome the weakness of the currently existing HFUS. Methods: 3D-HFUS was newly developed and applied to various skin tumors and inflammatory hair diseases to assess its validity and advantages for dermatological use. Results: Three-dimensional images were successfully obtained from skin tumors, including basal cell carcinoma, subungual squamous cell carcinoma, Bowen’s disease, and malignant melanoma, as well as inflammatory hair loss diseases including alopecia areata in different disease phases and lichen planopilaris. Vertical and horizontal images were generated from the original 3D image data and assessed in comparison with histopathological and/or dermoscopic images. By additionally obtaining horizontal data, lateral tumor margins at any depth were visualized in tumors. In inflammatory hair loss diseases, signs potentially associated with disease activity and pathology were detected. In addition, horizontal evaluation helped grasp hair cycle status and hair follicle densities. Conclusions: These findings suggested that this novel technology holds promise as a robust noninvasive tool to diagnose and evaluate various cutaneous diseases.